Reevaluating Gender Dynamics: A Critical Analysis of Misogynistic Narratives in Hadith Literature - Rodliyana, M. Dede (UIN Sunan Gunung Djati Bandung, 2023)
The discourse on religion and feminism often includes an analysis of the social construction of women in religious teachings. Feminist scholars argue that religious doctrines and interpretations, including those in Islam, have historically propagated subordinate views of women. This study examines such perceptions within Islamic Hadiths, specifically focusing on hadiths deemed misogynistic, as reported by al-NasÄâ€™Ä« and other primary sources. This qualitative study employs a bibliographic approach, scrutinizing the authenticity and contextual meaning of the Hadiths. It involves a critical examination of the chain of transmission (sanad) and the text (matan) of the hadiths. The study also considers the historical and cultural context of these narrations and engages feminist perspectives to offer alternative interpretations. The hadiths from al-NasÄâ€™Ä« are generally classified as hasan (sound), based on the credibility of the narrators. Variations in the text across different reports are critically examined for consistency in meaning. The study finds that while the hadiths reflect the patriarchal culture of their time, their interpretation is subject to the context and can align with Islamic teachings on justice and gender equality. The analysis suggests that these Hadiths, when contextualized, do not inherently convey misogynistic intentions. The study concludes that the perception of misogyny in the hadiths is influenced by their interpretation and historical context. A more nuanced understanding reveals that these hadiths can be interpreted in ways that support harmony and equality within the family, aligning with broader Islamic principles.